Molecular identification, abundance and distribution of the coral-killing sponge Terpios hoshinota in Bengkulu and Seribu Islands, Indonesia - RISNITA TRI UTAMI; NEVIATY P. ZAMANI; HAWIS H. MADDUPPA (Society for Indonesian Biodiversity, 2018)
Utami RT, Zamani NP, Madduppa HH. 2018. Molecular identification, abundance and distribution of the coral-killing sponge Terpios hoshinota in Bengkulu and Seribu Islands, Indonesia. Biodiversitas 19: 2238-2246. Coral killing sponge Terpios hoshinota is one of threats to coral reefs. The outbreaks of  T. hoshinota has been reported in the Indo-Pacific region. However, the current distribution of this species in Western of Sumatera Island is unknown, compared to Seribu Islands. This study aimed to identify coral-killing sponge molecularly and to compare the distribution and abundance of T. hoshinota in Bengkulu (Western of Sumatera) and in Seribu Islands (Northern of Java Island) and to record the preferences of coral substrate of T. hoshinota. Coral reefs and T. hoshinota data were collected using underwater photo transect method with 0.5x0.5m2 quadrate transect. Coral reefs covered by T. hoshinota was analyzed by using Correspondence Analysis, while the determination of biophysical and chemical environment was analyzed by Principal Component Analysis. The identity of the sponge was T. hoshinota. T. hoshinota has been expanding in many reefs across Indonesia especially in Tikus Island and Belanda Island. The most prevalent coral genera in the Seribu Islands infected by T. hoshinota was Acropora while those in Bengkulu were Porites and Pocillopora. Pearson correlation between the live coral cover and T. hoshinota cover was revealed not significant, while T. hoshinota cover and orthophosphate was significant. This study suggests that orthophosphate may play a role invasion of T. hoshinota outbreaks.